Advances in the Relationship between MicroRNA and Cisplatin Resistance of Lung Cancer - Fang ZHANG; Yang LI; Qinghua ZHOU (Chinese Journal of Lung Cancer, 2014)
MicroRNAs (miRNAs) are a class of small, about 22 nucleotides endogenous noncoding RNAs that negatively regulate their target genes’ expression through post-transcriptional suppression. MicroRNA has a broad effect on tumorigenesis and tumor biological processes, including tumor development, differentiation, metastasis and chemoresistance. Chemoresistance represents a major obstacle in effective clinical treatment of tumors, how to conquer the chemoresistance in tumor arouses people’s interst. A growing number of studies have proved that microRNAs play a crucial role in tumor chemoresistance. This view will discuss the the progress research between microRNA and tumor therapy, especially the cisplatin chemotherapy in tumor.